(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
The Indian Life Insurance sector has witnessed a major revamp in 1999 with the establishment of Insurance Regulatory and Development Authority (IRDA) and subsequent entry of Private sector players. These changes are affecting the way service is being delivered. Technology usage, new innovative product introduction and competition are seen as drivers of quality of service being provided to the customers. In this study using SERVQUAL model, we have examined the importance of service based on the 5 dimensions viz, Tangibles, Reliability, Responsiveness, Assurance and Empathy. Using 120 Life Insurance policy holders from 3 Life insurance companies in Agra the study identified that the gaps exist even after 15 years of privatization of this sector. The study indicated that a lot needs to be done for improving customer focus and services activity in the Life Insurance sector. Regular customer surveys with increased sample sizes across the country will enable the Insurance companies to fill the gaps.